Rural Populism and Tolerance for Political Violence - Jesse Callahan Bryant; J. Tom Mueller; Paul Berne Burow (Socius)
This study shows that populist attitudes are associated with reduced tolerance for political violence in rural areas of the United States. Using a representative sample from rural counties in the American West, the authors advance conceptual frameworks in populism studies and address the challenges of measuring social phenomena in rural areas. Using structural equation modeling and a “bare bones” measure of populism, the authors test hypotheses on links between economic and sociocultural grievances, ideological conservatism, populist attitudes, and tolerance for political violence. The findings confirm associations among economic grievances, conservatism, and populist attitudes, while showing that populism attenuates the link between economic grievance and tolerance for political violence. Thus, this study reveals an unexpected ideological role of populist attitudes in diminishing support for political violence. This advances sociological understanding of how populism interacts with broader ideological systems in the United States and draws greater attention to how political concepts are operationalized empirically.